ANATOMY PRACTICAL SESSION USING JIGSAW METHOD - Saharnauli Janna Verawaty Simorangkir (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: The challenge faced by anatomy educator today is the number of medical education students added with medical competencies about the anatomy of human body that must be achieved and the limited teaching staff. Other problems are the reduced time allocation for anatomy lectures and decreasing student knowledge about the anatomy of the human body. To answer these problems, one solution that can be done is to test the most effective method to help students understand each topic given in lectures and practicum anatomy. The aim of this research was to find out the difference in learning achievement and learning motivation between Jigsaw group and control group during anatomy practicum.Method: This research was a quasi-experimental research. The samples of this research were all medical students of UHKBPN batch 2017 who were actively undergoing lectures. The number of samples of this study were 39 people, where the control group was 20 people and the Jigsaw group were 19 people. Data collection instruments were the SMTSL questionnaire and the pretest and posttest questions.Results: Bivariate analysis results showed an increase in posttest results in both groups (p <0.05). Univariate analysis results for the questionnaire scores showed that most students in the two groups had moderate motivation, while the results of the bivariate analysis showed no difference between the two groups (p> 0.05).Conclusion: The Jigsaw cooperative learning method is effective to be implemented in anatomy practicum.